Conversion of protein of forage in food albumen of carcass of cows of different lines of znam'yanskiy of type of polesskoy meat breed - Доротюк, Е. М.; Цуканова, М. О.; Подрезко, Г. М. (Scientific Progress & Innovations, 2012)
The results of study of conversion of protein of forage are expounded in the food albumen of carcass of cows of znam’yanskiy type of different lines. It is proved that cows of Radist line 113 have the best conversion ability of transformation of protein of forage in a food albumen. It is established that carcasses of cows of Radist line had the most maintenance of albumen(53,8 kg or more than at nonlinear analogues on 10,3кг (19,1%), Balovnya line 6 on 6,3 kg (11,7%), Podarennogo line 400 on 5,5 kg (10,2%).